Body mass index and benign prostatic hyperplasia correlate with urinary microbiome diversity and lower urinary tract symptoms in men - Kate R. Bowie; Mark Garzotto; Eric Orwoll; Lisa Karstens (Communications Medicine)
Abstract Background Several studies have identified bacteria and other microbes in the bladder and lower urinary tract in the absence of infection. In women, the urinary microbiome has been associated with lower urinary tract symptoms (LUTS), however, similar studies have not been undertaken in large cohorts of men. Here we examine the urinary microbiome and its association with LUTS in a subset of 500 men aged 65–90 years from the Osteoporotic Fractures in Men (MrOS) study. Methods Bacterial DNA was isolated from urine samples. The V4 region of the 16S rRNA gene was sequenced using Illumina Miseq. Microbiome characteristics, including diversity measures and urotypes, are examined for associations with clinical characteristics and lower urinary tract symptoms. Results Here we identify significant associations between benign prostatic hyperplasia (BPH), age, and body mass index (BMI) with several diversity metrics. Our analysis reveals complex relationships between BMI, BPH, LUTS, and alpha diversity which give insight into the intricate dynamics of the urinary microbiome. Conclusions By beginning to uncover the interrelationships of BPH, BMI, LUTS, and the urinary microbiome, these results can inform future study design to better understand the heterogeneity of the male urinary microbiome.